The Study Philosophy and Methods for Creating Musical Works of Xin Di - Qiu , Xijie; Phokha, Pramote (Journal of Ecohumanism, 2025)
This study aims to explore Xin Di's biography and musical works, analyze and synthesize the concepts and perspectives that influence Xin Di's work, and provide guidelines for policy utilization. The research methods include document study, data collection, and data analysis. Through observation and interviews, the researcher delves into Xin Di's musical academic career and philosophical ideas, collecting data on Xin Di's musical works and teaching materials. The results indicate that Xin Di's music education philosophy emphasizes student interest-driven learning, motivating students through joyful learning, and systematically training their skills. Xin Di's educational methods focus on a progressive model, from broad-based education to individual elite cultivation, and from sensory experience to rational understanding. The study concludes that Xin Di's educational philosophy and teaching methods align with modern humanism and constructivism educational theories, significantly enhancing students' musical proficiency and creativity. The study recommends that educational policymakers and practitioners promote interest and joy-based teaching methods to stimulate students' learning motivation and creativity.